Service users' involvement in social work education: focus on social change projects. Issue 1 (2nd January 2019) - Ramon, Shulamit; Moshe Grodofsky, Merav; Allegri, Elena; Rafaelic, Andreja
ABSTRACT: This article presents and analyzes four projects focusing on diverse forms of service users' involvement in social work training and research in different countries (Israel, Italy, Slovenia and UK). It highlights the value of service user involvement (SUI) to specific social change objectives and to social work education. The conceptual framework focused on the Standpoint Theory, while methodologically participatory action research was applied, and evaluation measures were developed. Key findings, facilitators and limitations to the involvement, students' views of it and similarities and differences among the four projects are outlined. The challenges embedded in introducing and sustaining social change objectives in a co-production framework within social work education are identified, alongside the added value of meeting them. The differentiated impact the projects had on students is highlighted as well as their significance for health and social care providers were relevant. It is encouraging that in each project SUI was positively valued. The projects indicate the wide range of SUI in the content and format of social work education, as well as its applicability cross-culturally to a range of key issues pertaining to both training and research in social work.